2014
DOI: 10.1088/1478-3975/11/4/044001
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic effect of H1-histone protein binding on nucleosome repeat length

Abstract: Within a simple biophysical model we describe the effect of electrostatic binding of H1 histone proteins on the nucleosome repeat length in chromatin. The length of wrapped DNA optimizes its binding energy to the histone core and the elastic energy penalty of DNA wrapping. The magnitude of the effect predicted from our model is in agreement with the systematic experimental data on the linear variation of nucleosome repeat lengths with H1/nucleosome ratio (Woodcock C L et al 2006 Chromos. Res. 14 17-25). We com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 62 publications
2
23
0
Order By: Relevance
“…Electrostatic interactions are modified with salts, allowing the prediction of small electrostatic contribution under physiological conditions in the case of DNA cyclization. 37 Adsorption processes on nanoparticles or surfaces involving DNA-like chains are commonly studied by computer simulations. 33 Interesting trends related to the formation of complexes between chains and nanoparticles, or more generally surfaces, have been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Electrostatic interactions are modified with salts, allowing the prediction of small electrostatic contribution under physiological conditions in the case of DNA cyclization. 37 Adsorption processes on nanoparticles or surfaces involving DNA-like chains are commonly studied by computer simulations. 33 Interesting trends related to the formation of complexes between chains and nanoparticles, or more generally surfaces, have been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have suggested that the electrostatic interactions between H1 and DNA/nucleosome are a major determinant of the stoichiometry of direct binding of H1 to the nucleosome based on a theoretical study. 49 They estimated the parameters of their electrostatic model for direct binding of H1 to DNA with experimental data showing a linear dependence of NRL on H1 stoichiometry. 50 It is widely accepted that NRL is very much heterogeneous and polydisperse.…”
Section: Discussionmentioning
confidence: 99%
“…They exert this effect by modulating local chromatin structure and thereby changing the accessibility of TFs. As a matter of fact, some other factors can also shape chromatin and then control gene activity, such as the electrostatic effect and concentration of H1 histone, DNA sequence, and long-range internucleosome interactions, which influence DNA compaction by regulating the distance between two neighboring nucleosomes, namely nucleosome repeat length (NRL) (Beshnova et al, 2014;Cherstvy and Teif, 2014), and the similarities in the structure of chromatin fibers (structural homology), which affect their pairing by electrostatic and protein-mediated bridging interactions (Cherstvy and Teif, 2013). Because of the close relationship between these factors and DNA structure, it is possible to construct a model predicting gene transcription level by them, too.…”
Section: Discussionmentioning
confidence: 99%